Association between ECE1 gene polymorphisms and risk of intracerebral haemorrhage. (June 2016) - Zeng, Yi; Ma, Mingming; Liu, Baoqiong; Xia, Jian; Xu, Hongwei; Liu, Yunhai; Du, Xiaoping; Hu, Zhiping; Yang, Qidong; Zhang, Le
Objective: To determine whether endothelin converting enzyme-1 ( ECE1 ) gene polymorphisms contribute to susceptibility to intracerebral haemorrhage (ICH) by influencing blood pressure. Methods: This case–control study enrolled patients with ICH and healthy control subjects from a Southern Han Chinese population. The ECE1 gene polymorphisms rs212528 and rs213045 were genotyped. The association between the genotypes and the risk of ICH was assessed. The effects of these two ECE1 gene polymorphisms on blood pressure were also analysed. Results: A total of 389 patients with ICH and 404 healthy control subjects participated in the study. There was no significant association between the ECE1 rs212528 and rs213045 polymorphisms and ICH even after adjusting for different confounding variables. In patients with ICH, the systolic blood pressure of patients with the rs212528 AA genotype was significantly lower than that of patients with the AG/GG genotypes. Conclusions: These results indicated that the ECE1 rs212528 and rs213045 polymorphisms had no major role to play in the genetic susceptibility to ICH, although rs212528 might influence blood pressure in patients with ICH.